In My Mosque - Yuksel, M. O.; Aly, Hatem (New York, NY : Harper, an imprint of HarperCollins Publishers, 2021)
A picture book featuring culturally rich artwork celebrates the joys, rituals, and traditions that are practiced in mosques throughout the world, and includes a glossary and information about many historical and significant mosques.
Includes bibliographical references (page 34).
Keywords: Mosques -- Juvenile fiction; Islam -- Juvenile fiction. -- Customs and practices; Mosques -- Fiction; Islam -- Fiction. -- Customs and practices; JUVENILE FICTION -- Religious; JUVENILE FICTION -- Social Themes; JUVENILE FICTION -- Holidays & Celebrations; Islam -- Customs and practices; Mosques; Mosques -- Juvenile fiction; Islam -- Juvenile fiction; Mosques -- Fiction; Islam -- Fiction; Picture books; Fiction; Juvenile works; Picture books